2022
DOI: 10.1126/sciadv.abm7538
|View full text |Cite
|
Sign up to set email alerts
|

Emi2 enables centriole amplification during multiciliated cell differentiation

Abstract: Massive centriole amplification during multiciliated cell (MCC) differentiation is a notable example of organelle biogenesis. This process is thought to be enabled by a derived cell cycle state, but the key cell cycle components required for centriole amplification in MCC progenitors remain poorly defined. Here, we show that emi2 ( fbxo43 ) expression is up-regulated and acts in MCC progenitors after cell cycle exit to transiently inhibit anaphase-promoting compl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 47 publications
1
11
0
Order By: Relevance
“…This would eventually lead to an entire decoupling between the nuclear and cytoplasmic compartments, as seen in developing fly blastoderms (31). Since decoupling between centrosome and nuclear cycles can also be obtained by dampening CDK activity in cycling cells (32,33) and that DNA replication and mitotic events can be restored in cells undergoing this MCC cell cycle variant by disinhibiting CDK activity (3,5), we suggest the existence of a cytoplasmic -or centriolar-CDK threshold, lower than the S-phase threshold. A quantitative control of CDK activity by APC/C and the regulated expression of its inhibitors Emi1/2 would thus allow the progression of a purely cytoplasmic MCC cell cycle variant.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…This would eventually lead to an entire decoupling between the nuclear and cytoplasmic compartments, as seen in developing fly blastoderms (31). Since decoupling between centrosome and nuclear cycles can also be obtained by dampening CDK activity in cycling cells (32,33) and that DNA replication and mitotic events can be restored in cells undergoing this MCC cell cycle variant by disinhibiting CDK activity (3,5), we suggest the existence of a cytoplasmic -or centriolar-CDK threshold, lower than the S-phase threshold. A quantitative control of CDK activity by APC/C and the regulated expression of its inhibitors Emi1/2 would thus allow the progression of a purely cytoplasmic MCC cell cycle variant.…”
Section: Discussionmentioning
confidence: 86%
“…Pharmaceutical modulation of the activity of these cell cycle factors induces major defects in numbers of generated centrioles and in the dynamics of their formation, as well as in motile ciliation in terminally differentiated MCCs. They can also induce mitosis-like features and abnormal DNA replication ( 3 , 5 ). Here we use single-cell RNA-seq experiments to investigate the co-option of cell cycle factors, coupled with functional assays to study the role of cyclins during MCC differentiation.…”
Section: Main Textmentioning
confidence: 99%
“…Most surprisingly, centriole disengagement, which is known to be Plk1 and APC/C dependent (Al Jord et al, 2017; Kim et al, 2022; Ruiz García et al, 2019), is tightly correlated with this nuclear association. First, the migration of procentriole loaded deuterosomes systematically precedes centriole disengagement.…”
Section: Discussionmentioning
confidence: 99%
“…Since live observations are difficult in respiratory MCCs, the stages of amplification have been finely described by immunostainings (Zhao et al, 2013, 2021). Molecular examination by immunostainings and loss of function experiments on both mouse brain and respiratory MCCs showed that the cell cycle regulators and the centriole duplication molecular cascade used by cycling cells are co-opted in differentiating MCCs to control centriole number, growth and disengagement (Al Jord et al, 2017; Kim et al, 2022; LoMastro et al, 2022; Revinski et al, 2018; Vladar et al, 2018; Vladar & Stearns, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…In the case of GEMININ, and likely MCIDAS, this requires APC/C CDC20 [2,61]. Moreover, recent work demonstrated that Emi2, a negative regulator of APC/CDH1, is upregulated by MCIDAS and plays an important role in multiciliation [62]. The emerging picture suggests that GEMC1 and MCIDAS both activate and are targets of cell cycle-specific regulatory proteins, providing an elegant mechanism to facilitate their stepwise actions and fine tune transcriptional output with massive centriole amplification.…”
Section: Discussionmentioning
confidence: 99%